Preserving Traditional Islamic Thought and Practice: - Rohman, Rohman (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2015)
This paper tries to construct the role of the codified SÅ«rahYÄsÄ«n and Taá¸¥lÄ«l texts in Indonesia.The present paper also attempts to investigate the sequential aspects of the transmission of sÅ«rahYÄsÄ«n from the single sÅ«rah until it is compiled with taá¸¥lÄ«l texts and become widely used among traditionalist Muslims in Indonesia. The paper provides the faá¸Äâil al-aâmÄl based on some muslim scholars. Some important questions will be dealt here, namely: why does sÅ«rah YÄsÄ«n has a special position? How was sÅ«rahYÄsÄ«n and taá¸¥lÄ«l texts compiled in Indonesia? In this paper, I argue that the sÅ«rahYÄsÄ«n compiled with taá¸¥lÄ«l texts is sort of textual forms which preserve the traditional Islamic thought and practices in Indonesia. Keywords: SÅ«rahYÄsÄ«n and Taá¸¥lÄ«l